Artists’ books et nursery porn : Ré-illustrer les Victoriens - Laurent Bury (Sillages Critiques)
In her book The Artist as Critic, Lorraine Kooistra defined as “bitextuality” the link between words and pictures within the covers of a book, a link that can exist according to five categories: quotation, impression, answering, parody and cross-dressing. To those five modes, this paper would like to add three more, which correspond to the relation between Victorian texts and twentieth-century images: the inversion of textual roles, exchangism and homotextuality. In the first category, one can find artists’ books and graphic novels, where the pictures openly dominate the words. Exchangism means illustrating a text by recycling pictures initially meant for another text. Homotextuality appears when an illustration sends the reader back to a previous, supposedly well-known illustration, rather than to the text it accompanies: when Edward Gorey re-illustrated Bleak House in 1953, his drawings explicitly referred to Phiz’ work for the original edition, one century before. However, none of those practices is characteristic of (post-)modernity, since they already existed in the Victorian age, under quite similar forms.